2002
DOI: 10.1179/096797802225003361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of purification and heat treatment on pore structure and composition of diatomite

Abstract: treatment in HCl acidic solutions. 1 0 There are several important studies in the literature on aspects of diatomite T he eVects of sintering and puri cation processes on including its puri cation, sintering, and processing. 6 ,1 1 -1 4 the porosity and speci c surface area of diatomaceousThe Turkish material was found to be essentially earth, mined in the A nkara region of T urkey, were amorphous but also contained crystalline illite, investigated. T he material was studied in three forms,and a small amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 3 publications
0
26
0
4
Order By: Relevance
“…The potential engineering and medical applications of diatom frustules have also recently been proposed, including metal film membranes, pinpoint drug delivery and processing of nanopowder silica [7]. The surface area of diatomaceous earth was reported to be relatively high, 22 m 2 /g [8] and it was shown to decrease slightly as a result of heat-treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…The potential engineering and medical applications of diatom frustules have also recently been proposed, including metal film membranes, pinpoint drug delivery and processing of nanopowder silica [7]. The surface area of diatomaceous earth was reported to be relatively high, 22 m 2 /g [8] and it was shown to decrease slightly as a result of heat-treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of acid treatment on different forms of highly and purified Egyptian diatomite was performed [19]. The conclusion of the above study stated that the structure of diatomite changes depended on the treated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…From Other investigations [19] were performed on prepared silica nanoparticles. It has been found that from the XRD spectra no sharp peaks resulting the absence of ordering crystalline structure.…”
Section: Resultsmentioning
confidence: 99%
“…No other treatments such as purification or heating was applied on received diatomite samples to avoid complicating the process although effects of purification and heat treatment on pore structure and composition of diatomite are known [17].…”
Section: Methodsmentioning
confidence: 99%